Aspectos fisiológicos de gramíneas nativas da América do Sul submetidas ao excesso de zinco - Milanesi, Gabriela Descovi (2020)
The accumulation of metals in soils such as Zinc (Zn) is observed in vineyards from several countries, including Brazil, in the vineyards of the Rio Grande do Sul campaign. The prolonged use of fungicides containing Zn in its composition, used to control fungal diseases in grapevines, cause the accumulation of this metal in the soil. The toxic effects of this metal can cause restrictions in the nutrient absorption process, in addition to promoting disturbances that compromise cell expansion and, consequently, lower growth. Zn can be a limiting factor for the development of native grass species that coexist between the rows of vineyards when present in high concentrations in the growth medium. The objective of this work was to characterize the physiological responses of grass species native to the pampa biome exposed to excess Zn, as well as to evaluate which species are more adapted to this condition. Study I was carried out in a hydroponic cultivation system containing three Zn concentrations (2, 150 and 300 μM) and four grass species (Paspalum notatum, Paspalum plicatulum, Axonopus affinis and Andropogon lateralis). At 40 days of cultivation, gas exchange, fresh and dry mass, biometric parameters of the root system, biochemical attributes, concentrations of Zn and nutrients in plant tissues were determined. Study II was conducted with three species of grasses Axonopus affinis, Paspalum notatum and Paspalum plicatulum submitted to five doses of Zn (0, 30, 60, 120 and 180 mg kg-1). At 90 days of cultivation, leaf gas exchange, determination of Zn concentration in soil and tissue, dry mass production, concentration of photosynthetic pigments, soluble proteins, concentration of nutrients in tissue, enzyme activity of POD and SOD, concentration were determined. of H2O2 and of TBARS. In study I, the increment of Zn doses in the nutrient solution increased the Zn concentration in the roots and shoots of the four species, however, it did not change the biomass growth. The rate of net assimilation of CO2 was increased with the addition of Zn concentrations for all species, mainly at the dose of 300 μM. Biochemical parameters, in general, were not affected by high Zn concentrations. The increase in Zn doses influenced the oxidative stress parameters (TBARS and H2O2) in a distinct way. Nutritional balance was affected in the four species with increasing Zn doses. Despite the physiological changes observed, the four species in this study showed great adaptation to the increased availability of Zn. In study II, the Zn content in the soil increased linearly with the application of Zn as well as the Zn concentration in the roots and shoots of the three species. Biochemical parameters, in general, were affected by high Zn concentrations. The increase in Zn doses influenced the oxidative stress parameters (H2O2 and TBARS) in a distinct way, and the increases in SOD and POD activities were correlated with the decrease in oxidative stress. The physiological evaluations analyzed indicate that the species Axonopus affinis is more tolerant to excess Zn.